Precipitation of Calcium Carbonate Inside Giant Unilamellar Vesicles Composed of Fluid-Phase Lipids - Witt, Hannes (Langmuir : the ACS journal of surfaces and colloids, 2020)
Biomineralization of CaCO3 commonly involves the formation of amorphous CaCO3 precursor particles that are produced in a confined space surrounded by a lipid bilayer. While the influence of confinement itself has been investigated with different model systems, the impact of an enclosing continuous lipid bilayer on CaCO3 formation in a confined space is still poorly understood as appropriate model systems are rare. Here, we present a new versatile method based on droplet-based microfluidics to produce fluid-phase giant unilamellar vesicles (GUVs) in the presence of high CaCl2 concentrations. These GUVs can be readily investigated by means of confocal laser scanning microscopy in combination with bright-field microscopy, demonstrating that the formed CaCO3 particles are in conformal contact with the fluid-phase lipid bilayer and thus suggesting a strong interaction between the particle and the membrane. Atomic force microscopy adhesion studies with membrane-coated spheres on different CaCO3 crystals corroborated this notion of a strong interaction between the lipids and CaCO3